A field guide to the large mammals of Vietnam - Parr, John W. K. (People and Nature Reconciliation (PanNature), 2008)
Contents: The history of mammalogy in Vietnam; Physiography; Climate; Zoogeography; Habitats; Conservation of mammals in Vietnam...